Socio-Economic Analysis In Maintaining A Woven Fabric Business In Rimbun Village, Sipispis District - Avina Br Purba, Marissa; ., Yusrizal; Tambunan, Khairina (JURNAL MANAJEMEN MOTIVASI, 2025)
This research aims to analyze the social and economic factors that influence the sustainability of the ulos woven cloth business in Rimbun Village, Sipispis District. The research method used is a qualitative descriptive approach through observation, interviews and document review of local craftsmen. The research results show that social factors such as cultural preservation, community involvement, and social relations between business actors make a significant contribution to business continuity. Meanwhile, from an economic perspective, challenges such as limited capital and market access encourage the need for product innovation and digital marketing strategies. This research also highlights the importance of maintaining cultural identity amidst modernization by maintaining the traditional values of ulos in an adaptive and creative form.